2014
DOI: 10.3989/mc.2014.06312
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of sewage sludge ash (SSA) as a cement replacement in precast concrete blocks

Abstract: ABSTRACT:The present study explored the technological feasibility of re-using sewage sludge ash (SSA) as a Portland cement replacement in commercially manufactured pre cast concrete blocks. The blocks analysed were made to the guidelines laid down in Spain's National Plan for Waste Water Treatment Plant Sludge, 2001Sludge, -2006, and European Union specifications (CE marking) for such products. Performance was compared in three families of blocks, with 0, 10 and 20% SSA. The findings proved that SSA is apt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 31 publications
(28 reference statements)
1
23
0
2
Order By: Relevance
“…Section 2.7) (e.g. [30], [31], [32], [33], [34], [36], [37], [38], [39]). A review of the relevant literature revealed only a small number of publications addressing the issues of material capture and processing (e.g.…”
Section: The Continuous Mfa Approachmentioning
confidence: 99%
“…Section 2.7) (e.g. [30], [31], [32], [33], [34], [36], [37], [38], [39]). A review of the relevant literature revealed only a small number of publications addressing the issues of material capture and processing (e.g.…”
Section: The Continuous Mfa Approachmentioning
confidence: 99%
“…El resto de los nuevos datos aportados se encuadran en el marco de la tesis doctoral sobre uso de CLD en este ámbito (Baeza-Brotons, 2012). El origen de todos estos estudios, basados en la utilización de CLD, se encuentra en la investigación sobre bloques de hormigón prefabricado (Pérez-Carrión et al, 2014), en el que la adición de CLD aporta unas interesantes respuestas mecánicas, con mejoras respecto al patrón de hasta el 25%. A pesar de que los resultados obtenidos en este estudio, con probetas cúbicas de hormigón, no serían comparables directamente con los resultados que se obtendrían con bloques de hormigón fabricados en planta, ya que difieren en sus dimensiones, configuración y proceso de fabricación, sin embargo, dado que existe coincidencia en la dosificación, este trabajo podría suponer un paso previo a la fabricación piloto de bloques en planta con aquellas adiciones con una mejor respuesta técnica en laboratorio.…”
Section: Introductionunclassified
“…The test results presented in literature [4,7,10,14,20] indicate a very limited suitability of SSTT ash for the construction industry, and particularly for modern concrete technology. Moreover, the high water demand and low pozzolanic activity of this ash preclude its use as an additive in concrete.…”
Section: Characteristics Of Ash From the Thermal Treatment Of Sewage mentioning
confidence: 99%
“…Therefore, research continues to develop effective, environmentally safe methods of managing/ using ash from the thermal treatment of sewage sludge. A popular solution for the processing of fly ash from SSTT is their use in the ceramics industry or in construction, for example, in the solidification of concrete blocks or their sintering into a granulated form [10,14,20]. The main purpose of these methods is the safe and economical immobilisation of hazardous compounds within the obtained material structure.…”
Section: Introductionmentioning
confidence: 99%